Ultimate Limit State Reliability-Based Approach Life Prediction of an Existing Frame Structure Under Seismic Hazard in Indonesia - Herucakra, Wira; Adnyani, Luh Putri (UI Scholars Hub, 2025)
Life assessment integrated with Structural Integrity Management (SIM) has been implemented in the oil and gas industry for the past decade to maintain the integrity and safety of an in-service structure used to support hydrocarbon exploration, production, and processing activity. Current structural life assessment, as ruled by the American Petroleum Institute (API), uses a fatigue-based approach for offshore structures subjected to wave loading. As the general principle of SIM is not limited to offshore structures, this study offers an alternative life assessment method for onshore structures, especially steel frame structures subjected to earthquake loads. Reliability analysis, combined with the effect of the time-related degradation mechanism of steel structure due to corrosion and mechanical damage, with non-linear structural analysis, produces comprehensive ultimate limit state behaviour and performance of an existing structure. A steel frame structure located in Indonesia was evaluated in this study, with the reference base shear developed based on the latest Indonesian Seismic Provision SNI 1726-2019; the life of the structure was estimated by determining the time interval required for the overstrength factor produced from the pushover analysis to approximate 1.0. The assessment demonstrated that the life of the existing structure exceeds its design life and is safe for operation.